Community-based surveillance to monitor trends in unaccompanied and separated children in eastern DRC. (December 2015) - Rubenstein, Beth L.; Spencer, Craig; Mansourian, Hani; Noble, Eva; Munganga, Gustave B.; Stark, Lindsay
Abstract: Children who are separated from their families and usual caregivers in emergencies face a multitude of risks. The humanitarian community lacks methods to systematically capture changes in the frequency and nature of such separations over time. A mobile phone-based community surveillance system was piloted in the Democratic Republic of the Congo. The goal was to identify new cases of unaccompanied and separated children on a weekly basis. Over an 11-week period, community focal points reported 62 cases of separation across 10 communities. The majority of children had been under the care of their parents prior to separation. More than half of the children were unaccompanied, meaning that they were living without an adult relative or customary caregiver. The pilot results suggest that implementing a mobile phone-based surveillance system in a humanitarian setting may be feasible and cost-effective and fills a critical gap in the measurement of separated and unaccompanied children in emergencies. A longer pilot to better understand how the system performs over time is recommended.